2023
DOI: 10.5194/egusphere-2022-1156
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The importance of detection thresholds for the quantification of source and timing of high-latitude dust emission using remote sensing

Abstract: Abstract. The observation and quantification of mineral dust fluxes from high-latitude sources remains difficult due to a known paucity of year-round in situ observations and known limitations of satellite remote sensing data (e.g., cloud cover and dust detection). Here we explore the chronology of dust emissions at a known and instrumented high latitude dust source: Lhù’ààn Mân (Kluane Lake) in Yukon, Canada. At this location we combine ground instrumentation, space-based remote sensing platforms, ground-base… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…However the subclass scattergrams of the Supplementary material (S4) suggest a more nuanced upper limit threshold: the 𝑈 𝑅𝑆 and 𝑈 𝑁𝑅𝑆 scattergrams, in particular, show upper-limit 𝑣 𝑑𝑢𝑠𝑡 (0) thresholds that can be anywhere in the 10 -11 -10 -10 µm 3 µm -3 range with a respective 𝜏 𝑈 ℓ range of 0.001-0.1. AboEl-Fetouh et al (2020) showed pan-Arctic 𝜏 𝑐 values (regional-scale, multi-year geometric means) that appeared to be robustly sensitive to natural events whose 𝜏 𝑐 variation was as Clay, feldspar, and then quartz minerals are the major constituents of the PM10 dust particles from the emissions in the Kluane Lake region (Bachelder et al, 2020;King, 2023). To derive the mean refractive index and the uncertainty for those values, we followed the method of Baldo et al (2020) volume fraction weighted refractive indices of the minerals found within the dust sampled at the site, through X-ray diffraction, assuming an internally mixed sample (Formenti et al, 2014).…”
Section: Remote Sensing Threshold For the Detection Of Local Dustmentioning
confidence: 99%
See 1 more Smart Citation
“…However the subclass scattergrams of the Supplementary material (S4) suggest a more nuanced upper limit threshold: the 𝑈 𝑅𝑆 and 𝑈 𝑁𝑅𝑆 scattergrams, in particular, show upper-limit 𝑣 𝑑𝑢𝑠𝑡 (0) thresholds that can be anywhere in the 10 -11 -10 -10 µm 3 µm -3 range with a respective 𝜏 𝑈 ℓ range of 0.001-0.1. AboEl-Fetouh et al (2020) showed pan-Arctic 𝜏 𝑐 values (regional-scale, multi-year geometric means) that appeared to be robustly sensitive to natural events whose 𝜏 𝑐 variation was as Clay, feldspar, and then quartz minerals are the major constituents of the PM10 dust particles from the emissions in the Kluane Lake region (Bachelder et al, 2020;King, 2023). To derive the mean refractive index and the uncertainty for those values, we followed the method of Baldo et al (2020) volume fraction weighted refractive indices of the minerals found within the dust sampled at the site, through X-ray diffraction, assuming an internally mixed sample (Formenti et al, 2014).…”
Section: Remote Sensing Threshold For the Detection Of Local Dustmentioning
confidence: 99%
“…Publications on the use of AERONET retrievals to characterize the properties of local dust events at high latitudes are rare. Huck et al (2023) employed meteorological measurements, along with AERONET AODs and Angstrom exponents (AOD spectral information), a remote camera and satellite imagery to investigate dust event detection limits in the Lhù'ààn Mân' region. One notable conclusion was that the oblique camera captured many dust blowing incidents that were not being detected by the CIMEL.…”
Section: Introductionmentioning
confidence: 99%